Phytochemical, Medicinal, and Green Approaches of Allamanda cathartica L.: A Mini Review - Balkrishna, Acharya; Saini, Akansha; Bhandari, Rachna; Arya, Vedpriya; Sharma, Ishwar Prakash (Current Indian Science, 2023)
Allamanda cathartica L. belongs to the family Apocynaceae and is a traditionally valuable medicinal plant that has been commonly used in the traditional medicinal system and contributes to the native healthcare system in various parts of the world. This plant is renowned for its antibacterial and anticancer effects and its usage in the treatment of jaundice, diabetes, hypertension, and polio. All of the economically and medicinally essential plant parts of this species are used in the preparation of a potent cathartic. This review focused on and intended to highlight the most current knowledge about A. cathartica, including its important ethnomedicinal, modern medicinal, and phytochemical potential along with its green approaches. This plant has been extensively used in herbal medicine and has various important phytopharmacological properties. The modern green technological approaches of this plant enhance agricultural productivity when its various nanoparticles are applied in fields that perform antimicrobial, antipathogenic activities. Nanoparticles serve as carriers for the delivery of drugs and as disease targets in contemporary medicine. This plant has recently been involved in modern medicine as a threat to cancer, which is a significant accomplishment for modern medical science. Hence, A. cathartica is an important plant that can be useful to cure various ailments and could be useful in modern science with its green approaches. We must further investigate this plant's bioactivities to determine the mode of action.
Keywords: Green approach